LINGUISTIC IMPOLITENESS: A Small Corpus Analysis on the Use of Impolite Languange by Children - Sri Minda Murni; Mutsyuhito Solin (Aceh International Journal of Social Science, 2012)
Abstract - Speaking politely is one of the pragmatic competencies of language users. The fact shows that Indonesian children Muslim writers produce impolite utterances through the characters and conflicts they create in the story books published by the Islamic publishers. The impolite utterances are interpreted as violating the principles of speaking politely as suggested by the Holy Qur’an. A small corpus analysis used in this study is aimed at finding preliminary data on the impolite language used by children for further research, while at the same time showing how the data present children pragmatic incompetence and violation of the Qur’anic principles of being polite. The findings show that affective and coercive impoliteness are presented in the stories. In addition, the study finds the following: a) the issues which drive impolite utterances are competition between siblings, schoolmates, and bad teacher-student relationship; b) the lexicon used include animals, physical appearance, and behavioral assessment. In the level of syntax, declarative, interrogative, and imperative moods are used; c) the Qur’anic principles violated by the impolite utterances are Qaulan Ma’rufa (speaking nicely), Qaulan Karima (speaking honorably), and Qaulan Layyina (speaking softly); and d) the violation of the Qur’anic principles is seen as reflecting the pragmatic incompetence of the characters and the authors in the way that they fail to create dialogues with refinement which reflect principles of Islam in the context of conflict.